Technology-Enhanced Application in L2 Pragmatic Instruction: A Systematic Literature Review - Pradana, Ilham Mulya Putra; Maharani, Gita Nathania; Harimurti, Keke Febrian (Pascasarjana UM, 2023)
This systematic literature review focuses on the use of technology-enhanced applications in second language (L2) pragmatic instruction. This paper will systematically analyze papers from several electronic databases between the years 2012 and 2023 that investigate the use of technology in L2 pragmatic instruction, with a focus on the type of technology used, its effectiveness in enhancing pragmatic competence, and its impact on learners' motivation and engagement. The review also considers the pedagogical implication that underlie the design and implementation of technology-enhanced pragmatic instruction. The findings suggest that technology-enhanced applications can effectively enhance learners' pragmatic competence, motivation, and engagement. However, the effectiveness of such applications is highly dependent on the pedagogical principles that inform their design and implementation, including the incorporation of authentic materials, task-based instruction, and learner-centered approaches. The review concludes with recommendations for future research and pedagogical practice in this area.